KORELASI KETERAMPILAN MENYIMAK TEKS DISKUSI DAN KETERAMPILAN MENULIS TEKS DISKUSI SISWA KELAS VIII SMP NEGERI 1 LUBUK SIKAPING - Dhiyan Putri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This article discusses the correlation research between discussion text listening skills and discussion text writing skills for class VIII students of SMP Negeri 1 Lubuk Sikaping. There are three objectives of this research. First, describe the skills of listening to discussion texts for class VIII students of SMP Negeri 1 Lubuk Sikaping. Second, describe the writing skills of the eighth grade students of SMP Negeri 1 Lubuk Sikaping in writing discussion texts. Third, analyze the correlation of discussion text listening skills with discussion text writing skills for class VIII students of SMP Negeri 1 Lubuk Sikaping. This type of research is quantitative with descriptive method. The design used in this research is correlation. The population of this research is the VIII grade students of SMP Negeri 1 Lubuk Sikaping who are registered in the 2021/2022 academic year, as many as 305 students. The sample in this study was determined by proportional random sampling of 15% of the population, namely 45 students. The data of this research are in the form of scores of discussion text listening skills test scores and discussion text writing skills test scores. The data were obtained through two types of tests, namely objective tests to measure discussion text listening skills and performance tests to measure students' discussion text writing skills. The results of this study were threefold. First, the skills of listening to discussion texts for class VIII SMP Negeri 1 Lubuk Sikapings are in good qualification (B) with an average score of 77.67. Second, the discussion text writing skills of the VIII grade students of SMP Negeri 1 Lubuk Sikaping are in good qualification (B) with an average of 82.31. Third, there is a correlation between the skills of listening to discussion texts and the skills of writing discussion texts of class VIII SMP Negeri 1 Lubuk Sikaping with the test results proving that rcount is greater than rtable, namely 0,756 > 0,294.